The role of teachers’ beliefs and professional development in students’ mathematics motivation in primary education - Laura H. L. Niemi; Marja Holm; Eeva Haataja; Pia Ilomanni; Anu Laine (LUMAT)
Motivation plays a crucial role in mathematical competence, with motivated students tending to perform better than those who lack motivation. Given that teachers can play a significant role in fostering student motivation, the aim of this study was to investigate teachers’ influence on students’ motivation to learn mathematics. Alongside the teacher’s influence, we also aim to explore the impact of individual factors on students’ motivation. This study examines the effects of both individual and teacher-related factors on fostering students’ mathematics motivation, at both the student and the classroom levels. We use multilevel modelling for analysis. Student level contains individual factors: grade level, gender, and mathematics achievement. Classroom level contains teacher-related factors: teacher beliefs and professional development. Motivation was addressed through five dimensions: intrinsic value, utility value, attainment value, relative cost and perceived competence. The data is part of the international longitudinal study, MathMot, which examines primary school students’ mathematics motivation across six European countries. The data of the present study consists of Finnish students from 3rd (n = 760) and 4th grade (n = 747) and their teachers (N = 95). According to the results, student motivation is most significantly impacted by mathematical achievement at the individual level, and by teachers’ in-service training and beliefs about teaching and learning mathematics at the classroom level. Establishing a direct connection between teacher self-efficacy and student motivation is challenging because it affects motivation indirectly, for example, through teaching methods. Additionally, the role of the teacher in fostering motivation is relatively small and unstable in the early years.